An Artificial Solid Electrolyte Interphase with High Li‐Ion Conductivity, Mechanical Strength, and Flexibility for Stable Lithium Metal Anodes. Issue 10 (29th December 2016) - Liu, Yayuan; Lin, Dingchang; Yuen, Pak Yan; Liu, Kai; Xie, Jin; Dauskardt, Reinhold H.; Cui, Yi
Abstract : An artificial solid electrolyte interphase (SEI) is demonstrated for the efficient and safe operation of a lithium metal anode. Composed of lithium‐ion‐conducting inorganic nanoparticles within a flexible polymer binder matrix, the rationally designed artificial SEI not only mechanically suppresses lithium dendrite formation but also promotes homogeneous lithium‐ion flux, significantly enhancing the efficiency and cycle life of the lithium metal anode.